Clinical features of patients with paroxysmal kinesigenic dyskinesia, mutation screening of PRRT2 and the effects of morning draughts of oxcarbazepine - Gang Pan; Linmei Zhang; Shuizhen Zhou (BMC, 2019)
Abstract Background The objective of this study was to summarize clinical features and PRRT2 mutations of paediatric paroxysmal kinesigenic dyskinesia (PKD) patients and observe the tolerability and effects of morning draughts of oxcarbazepine. Methods Twenty patients diagnosed with PKD at Children's Hospital of Fudan University between January 2011 and December 2015 were enrolled. These patients' medical records were reviewed. Peripheral venous blood was obtained from all enrolled patients, and polymerase chain reaction (PCR) and Sanger sequencing were used to sequence proline-rich transmembrane protein 2 (PRRT2) gene mutations. Clinical features of PKD patients with and without PRRT2 mutations were compared. All enrolled patients were treated with morning draughts of oxcarbazepine (OXC). The starting dose was 5 mg/kg·d, and the dose was increased by 5 mg/kg·d each week until attacks stopped. Effective doses and adverse effects were recorded. Results For all enrolled patients, dyskinesia was triggered by sudden movement. Dyskinetic movement usually involved the limbs and was bilateral; the majority of enrolled patients exhibited both dystonia and choreoathetosis. We identified PRRT2 mutations in 5 patients, including 4 familial patients and 1 sporadic patient. All 20 patients took low doses of OXC (5-20 mg/kg·d) as draughts in the morning, and dyskinesia attacks stopped in 19 patients. Conclusions Paediatric PKD patients have various phenotypes. PRRT2 mutations are common in familial cases. OXC taken as morning draughts can be a treatment option for paediatric PKD patients.